2012
DOI: 10.1128/jvi.00438-12
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Phosphorylation of the Basic Protein P6.9 of Autographa californica Nucleopolyhedrovirus

Abstract: A protamine-like protein named P6.9 is thought to play a role in the condensation of genomes of the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV) during an infection. Previous studies have shown that P6.9 is phosphorylated immediately upon synthesis and dephosphorylated upon the entry of the P6.9-DNA complex into the capsid. Here, we investigate the dynamic distribution of P6.9 in AcMNPV-infected Spodoptera frugiperda cells using an influenza virus hemagglutinin (HA)-tagged P6.9. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…However, the capsid structures resulting from loss of the aforementioned genes were located not only in the RZ but also in the VS (interspace of the electron-dense mats) (16,(18)(19)(20)22), whereas in vAc54KO-transfected cells, no capsid structures were observed in the VS (Fig. 2B).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the capsid structures resulting from loss of the aforementioned genes were located not only in the RZ but also in the VS (interspace of the electron-dense mats) (16,(18)(19)(20)22), whereas in vAc54KO-transfected cells, no capsid structures were observed in the VS (Fig. 2B).…”
Section: Resultsmentioning
confidence: 94%
“…In addition, abnormal electron-dense bodies were found in the VS, and empty capsid structures were found in the RZ in cells transfected with vAc54KO, indicating that ablation of ac54 disrupted the normal assembly of nucleocapsids. In addition to ac54, some other AcMNPV genes (i.e., 38K, ac53, ac83, pk-1, and p6.9) have also been implicated in nucleocapsid assembly, and their individual deletion results in the cessation of assembly and the appearance of empty capsid structures in both the RZ and VS (16)(17)(18)(19)(20)22). However, in the present study, neither capsid structures nor VP39 was observed inside the VS in Sf9 cells transfected with vAc54KO, implying a special role of VP1054 in the baculovirus life cycle besides nucleocapsid assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many different dephosphorylated forms of P6.9, as well as phosphorylated P6.9, were present in association with ODVs, although only dephosphorylated P6.9 was associated with BVs . P6.9 was also detected in the BV proteomes of HearNPV and AcMNPV, but not in the BV proteome of AgMNPV, which might be a result of P6.9 cleavage (Braconi et al, 2014;Liu et al, 2012). The biological significance of the cleavage of P6.9 remains unclear.…”
Section: Proteins Shared By Seven Identified Baculovirusesmentioning
confidence: 99%
“…To explore the mechanism by which ac132 influences assembly and envelopment of nucleocapsids, experiments were performed to detect interaction between AC132 and other viral proteins. The candidate proteins selected for examination included the major capsid protein VP39 (39), the viral genome-binding protein P6.9 (41,42), BV and ODV envelope proteins E25 (40) and E18 (43), VS-associated proteins IE1 (44) and PP31 (45), and BV/ODV-C42, involved in virus-induced nuclear actin polymerization (46). The extracts of Sf9 cells infected by AcMNPV were immunoprecipitated with AC132-specific antibodies.…”
Section: Ac132mentioning
confidence: 99%